Two new species and a new record of Helvella (Helvellaceae, Pezizales) from South Korea - Park, Sang-Young; Kim, Sohee; Park, Eunsu; Kwag, Young-Nam; Eo, Ju-Kyeong; Lee, Hwayong (Phytotaxa, 2025)
In this study, we conducted morphological examinations and multi-locus phylogenetic analyses using ITS2, nrLSU, and hsp90 markers on seven Helvella specimens collected in Korea in 2024. Our analyses confirmed the presence of six phylogenetic species, viz. including two novel species H. griseomacropus and H. koreana and one new record for Korea, H. pseudoelastica. The two new species formed independent clades within the Macropus and Solitaria lineages, respectively, and were clearly distinguishable from related taxa based on both morphological characteristics and molecular data. Notably, H. koreana formed a sister clade to H. taiyuanensis, but its distinct morphology and phylogenetic placement support its recognition as a new species. In addition, we secured a specimen of H. acetabulum, previously reported in Korea only in literature, but without any voucher specimens; its presence is now confirmed with our collection.